Curcumin–QingDai combination for patients with active Crohn’s disease: a retrospective, real-world multicenter cohort study - Salomon, Nir; Marom, Maayan; Odeh, Safwat; Molnar, Madlen; Shitrit, Ariella Bar-Gil; Nayshool, Omri; Ungar, Bella; Ben-Horin, Shomron; Rainis, Tova (Frontiers in Gastroenterology, 2025)
BackgroundThe combination of curcumin and QingDai (CurQD) promotes aryl hydrocarbon receptor (AhR) activation and is effective in ulcerative colitis; however, its benefit in Crohn’s disease (CD) has not been studied.MethodsThis is a retrospective, multicenter cohort study of patients who received CurQD for active CD, defined as the two-item patient-reported outcome (PRO2) stool frequency (SF) ≥ 2 and abdominal pain (AP) ≥ 1. The primary endpoint was the rate of clinical remission at the end of induction (weeks 8–12), defined by a PRO2 SF ≤ 1 and an AP = 0. The secondary endpoints included biomarker response [fecal calprotectin (FCP) drop ≥50% in a patient with FCP >250 μg/g at baseline] and remission (FCP drop ≥50% and FCP < 250 μg/g at the end of induction) and CurQD retention. Exploratory analysis of the public domain Genotype–Tissue Expression (GTEx) dataset was performed to elucidate the mRNA expression of AhR along the gut axis.ResultsA total of 30 patients were identified for the safety dataset (13/30, 43% bio-experienced), and 25 were eligible for inclusion in the efficacy analysis. Clinical PRO2 remission at the end of induction was achieved in 12/25 (48%) patients and clinical response in 19/25 (76%), with an overall reduction in the median PRO2 score from 15 (95%CI = 13–19.7) to 4 (95%CI = 2–8.7, p < 0.001). Biomarker remission and response were observed in 11/20 (55%) and 15/20 (75%) patients, respectively, with baseline FCP > 250 μg/g, with an overall reduction in the median FCP from a baseline 639 μg/g (95%CI = 128–5480) to 138 μg/g (95%CI = 5–1470, p = 0.001). Biomarker remission was observed in 8/11 (73%) patients with colonic-involving L2/L3 disease versus 3/9 (33%) L1 extent (OR = 4.5, 95%CI = 0.8–24, p = 0.08). After 8 months’ median follow-up (range = 2–26 months), 16/19 (84%) responding patients were still taking CurQD. Three patients experienced headaches, and three had abdominal pain/diarrhea. Two of the six stopped CurQD due to these symptoms. One patient had elevated liver transaminases three times the upper limit of normal, which resolved upon halving the CurQD dose. In the public domain GTEx dataset, the mRNA expression of the target AhR in the colon versus the small intestinal mucosa was comparable, thereby not supporting differential AhR expression as a cause for a possible higher efficacy of CurQD in the colon,ConclusionIn this first-reported real-world experience, the AhR agonist CurQD was effective in inducing and maintaining the clinical and biomarker response and remission in over 50% of patients with CD, including in biologic-experienced patients.